Intermodulation Distortion in a Josephson Traveling-Wave Parametric Amplifier - Remm, Ants; Krinner, Sebastian; Lacroix, Nathan; Hellings, Christoph; Swiadek, François; Norris, Graham J.; Eichler, Christopher; Wallraff, Andreas (Physical Review Applied, 2023)
Josephson traveling-wave parametric amplifiers (TWPAs) enable the amplification of weak microwave signals close to the quantum limit with large bandwidth, which has a broad range of applications in superconducting quantum computing and in the operation of single-photon detectors. While the large bandwidth allows for their use in frequency-multiplexed detection architectures, an increased number of readout tones per amplifier puts more stringent requirements on the dynamic range to avoid saturation. Here, we characterize the undesired mixing processes between the different frequency-multiplexed tones applied to a Josephson TWPA, a phenomenon also known as intermodulation distortion. The effect becomes particularly significant when the amplifier is operated close to its saturation power. Furthermore, we demonstrate that intermodulation distortion can lead to significant crosstalk and reduction of fidelity for multiplexed readout of superconducting qubits. We suggest using large detunings between the pump and signal frequencies to mitigate crosstalk. Our work provides insights into the limitations of current Josephson TWPAs and highlights the importance of performing further research on these devices.
CRIS-Team Scopus Importer:2023-10-13